ANALISIS PENGARUH PRAKTIK KERJA LAPANGAN DAN PENGUASAAN MATA PELAJARAN PRODUKTIF TERHADAP KESIAPAN KERJA SISWA SMK DALAM MEMASUKI DUNIA KERJA - Sabrianil; Syahrul; Anas Arfandi (UNM Journal of Technology and Vocational, 2022)
The study aims to discover: 1) the description of students' internship, the value of productive subjects of TKJ students, and the level of students’ work readiness in Computer and Network Engineering skills at SMKN Takalar; 2) the influence of internship on the student's work readiness of Computer and Network Engineering skill competencies at SMKN Takalar; 3) whether there is an influence of the mastery of productive subjects on work readiness of students' competence in Computer and Network Engineering at SMKN Takalar; and 4) whether there is an influence of internship and the mastery of productive subjects collectively on work readiness of students' competence in Computer and Network Engineering at SMKN Takalar. The study employed ex-post facto research method. The totalpopulation was 194 people and the sample was 130 people. The data collecting employed documentation, questionnaires, and interviews. Hypothesis testing was conducted after conducting the analysis prerequisite test. The results of the study indicate that: 1) the students’ internship is 85 students (65.38%) which is in "very good" category, the mastery of students' productive subjects isvery good, based on the value of students' productive subjects there are 130 students ( 100%) in "very good" category, the students’ work readiness are 72 students (55.38%) which is in ready category; 2) there is an influence of internship on students' work readiness of r = 0.333 and the value of Sig. 0.000< 0.05 with a contribution of 11.1%; 3) there is an influence of the mastery of productive subjects on students' work readiness of r = 0.179 and the value of Sig. 0.041< 0.05 with a contribution of 3.2%; 4) there is an influence of internship and the mastery of productive subjects collectively on students’ work readiness of r = 0.372 and the value of Sig. 0.000 < 0.05 with a contribution of 13.8%.